Paraneoplastic limbic encephalitis with SOX1 and PCA2 antibodies and relapsing neurological symptoms in an adolescent with Hodgkin lymphoma. (July 2017) - Kunstreich, M.; Kreth, J.H.; Oommen, P.T.; Schaper, J.; Karenfort, M.; Aktas, O.; Tibussek, D.; Distelmaier, F.; Borkhardt, A.; Kuhlen, M.
Abstract: Background: Immune cross-reactivity between malignant and normal tissues causes the rare, so called paraneoplastic syndrome (PS). In approximately 60% of the patients, various onconeural antibodies are detectable in the cerebrospinal fluid (CSF) and are associated with typical tumour entities. Methods: We report an unusual case of paraneoplastic limbic encephalitis (PLE) in a 17-year-old adolescent with classical Hodgkin lymphoma. Results: He presented with a variety of neurologic and neuropsychiatric symptoms, profound B-symptoms and typical MRI findings including hyperintense lesions with contrast enhancement in the medial temporal lobe and limbic system. Under immunosuppressive therapy and subsequently chemotherapy the neurological situation only temporarily improved and worsened again after interruption of immunosuppression several times. Thus, multiple courses of multidrug immunosuppressive therapy were administered. To date, five years after initial presentation, the young man is able to walk with walking aids and orthoses and is still on oral prednisolone therapy. Analyses of the CSF and serum revealed anti SOX-1 antibodies at initial presentation but PCA-2 antibodies seven months after diagnosis. Conclusion: Neurologic and/or neuropsychiatric symptoms combined with typical MRI findings should raise the suspicion of PS and lead to further diagnostics for an underlying tumour even in children.